A multivariate approach to English Clippings - Hilpert, Martin; Correia Saavedra, David; Rains, Jennifer (Glossa (London), 2021)
This paper addresses the morphological word formation process that is known as clipping. In English, that process yields shortened word forms such as lab (< laboratory), exam (< examination), or gator (< alligator). It is frequently argued (Davy 2000, Durkin 2009, Haspelmath & Sims 2010, Don 2014) that clipping is highly variable and that it is difficult to predict how a given source word will be shortened. We draw on recent work (Lappe 2007, Jamet 2009, Berg 2011, Alber & Arndt-Lappe 2012, Arndt-Lappe 2018) in order to challenge that view. Our main hypothesis is that English clipping follows predictable tendencies, that these tendencies can be captured by a probabilistic, multifactorial model, and that the features of that model can be explained functionally in terms of cognitive, discourse-pragmatic, and phonological factors. Cognitive factors include the principle of least effort (Zipf 1949), an important discourse-pragmatic factor is the recoverability of the source word (Tournier 1985), and phonological factors include issues of stress and syllable structure (Lappe 2007). While the individual influence of these factors on clipping has been recognized, their interaction and their relative importance remains to be fully understood. The empirical analysis in this paper will use Hierarchical Configural Frequency Analysis (Krauth & Lienert 1973, Gries 2008) on the basis of a large, newly compiled database of more than 2000 English clippings. Our analysis allows us to detect regularities in the way speakers of English create clippings. We argue that there are several English clipping schemas that are optimized for processability.